1996
DOI: 10.1002/(sici)1522-7111(199622)6:3<185::aid-hfm1>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in hybrid intelligent scheduling

Abstract: Hybrid human‐computer intelligent systems for scheduling have evolved in response to the inability of algorithmic methods to handle the complexity of production in real manufacturing environments. They combine the abilities of humans to recognize patterns in data and to make inferences with computer methods for decision making. This article discusses: (1) the factors influencing scheduling decisions in small‐batch manufacture and the role of humans in the scheduling process, (2) the position of the human sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Many studies have noted the importance of graphical representation in determining human scheduling strategies (e.g., Cegarra & Hoc, 2003;Dessouky et al, 1995;Gibson & Laios, 1978;Higgins, 1996;Sanderson, 1991). Thus, it is very important that result comprehensibility is taken into account because of the consequences it could have on schedule evaluation.…”
Section: Results Comprehensibilitymentioning
confidence: 99%
“…Many studies have noted the importance of graphical representation in determining human scheduling strategies (e.g., Cegarra & Hoc, 2003;Dessouky et al, 1995;Gibson & Laios, 1978;Higgins, 1996;Sanderson, 1991). Thus, it is very important that result comprehensibility is taken into account because of the consequences it could have on schedule evaluation.…”
Section: Results Comprehensibilitymentioning
confidence: 99%
“…lotsizing or material flow control) has attracted a wealth of interest in the last years, such complex models are difficult and expensive from the implementation viewpoint (see e.g. Higgins, 1996). There are a number of reasons for this:…”
Section: Modular Design and Implementationmentioning
confidence: 99%
“…Planners play a crucial role, taking the large set of routing constraints into account and adapting to changes in the problem constraints (Jackson et al, 2004;Sanderson, 1989). They also make a decisive contribution when problems are over-constrained, as their extensive knowledge allows them to relax constraints in order to arrive at an efficient solution (Gacias, 2010;Higgins, 1996Higgins, , 2001MacCarthy & Wilson, 2001). Planners play such a vital part in routing that full automation of route selection is impossible.…”
Section: Planners' Constraint Processing In Route Selectionmentioning
confidence: 74%
“…For this reason, various authors have suggested that humans should be supported by Gantt charts (e.g., Adelsberger & Kanet, 1989;Kurbel & Ruppel, 1996). However, these charts have also been criticized, for helping humans to communicate the plan to other individuals but not necessarily to reach planning decisions (Higgins, 1996). Therefore, as Trenteseaux, Moray, and Tahon (1998) suggested in the industrial domain, and as demonstrated by our results, new graphical forms need to be developed for route selection.…”
mentioning
confidence: 99%